STUDY OF OPEN-AIR MUSEUM ON KAYUTANGAN STREET CORRIDOR - Cindy Elena Kartika; Lilianny Sigit Arifin (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
The Kayutangan Corridor is one of the areas in Malang that holds many historical values, namely as a shopping center in the Dutch colonial era. However, the glory and history of kayutangan began to fade with the times. This research's general objective is to provide a design proposal for the Kayutangan corridor that can present historical stories of the buildings along the corridor, such as an open-air museum, with the building as its object. The research method used is descriptive qualitative research with a signage theory approach. The final result of this study is the proposed signage and pedestrian design in the Kayutangan corridor.